Socio economic characteristics, micro-credit and technical efficiency of poultry farmers in Lagelu local government area of Oyo State, Nigeria (2010)
The study examines the linkage between micro credit, socioeconomic characteristics of poultry farmers and their technical j efficiency in Lagelu local government area of Oyo State. 115 respondents were selected through simple random sampling method. Stochastic frontier production function was used for the analysis; From the results of stochastic production frontier analysis carried out, it was found that land and labour have positive relationship with farmers’ efficiency in the study area. The positive sign of the coefficient of these variables shows that increase in land or labour will necessary bring about increase in efficiency, which means land and labour are very important factors in increasing the efficiency of livestock farmers. All other variables like breeding stock, drug and feed show positive relationship with efficiency of a livestock farmer which is the expected sign. But they are all not significant at different level. The average technical efficiency of poultry farmer was 0.3098. This shows that farmers are operating far below the frontier line. Five variables significantly affect the technical inefficiency of farmers. These include age, marital status; years spent in school, farming experience and access to micro credit. Age was significant at 1 percent level and positively related to the inefficiency. This means older farmer tend to be less efficient than the younger one. However, years spend in school and farming experience were significant at 1 percent and 10 percent respectively, but were negatively related to inefficiency. This means that increase in any one of these variables will reduce the level of inefficiency of poultry farmers] Marital status and access to micro credit were significant at 1 percent level of significance but the negative coefficient of marital status means that single farmers are more efficient than married one while the positive sign of access to micro credit means that efficiency increase with farmers that have access to micro credit in the study area. Based on the findings of this study, poultry farmers in the study area should be made to have access to micro credit since findings have shown that it impacts on their efficiency positively. It is also suggested that young unemployed graduates should be encouraged to go into poultry production.